Methodological Issues of the System of Formation Informatical Readiness of Future Interpreters in Universities - Dolynskyi, Yevhen (Pedagogical Discourse, 2014)
The relevance of the article is characterized by the current needs of information society in the preparation of informative competent professionals, particularly in the field of translation. The article considers the scientific, social and educational views on the formation of informative readiness of future interpreters in higher education. The problem of using of information technologies in teaching is analyzed. Methodological issues of the system of formation informatical readiness of future interpreters in universities are considered. The necessity of future translators using information and communication technologies in the system of professional education, forming of their informative readiness are analyzed.